2020
DOI: 10.1038/s41598-020-76753-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cervical elastography and spontaneous onset of labor

Abstract: Cervical elastography might be an objective method for evaluating cervical ripening during pregnancy, but its usefulness has not been fully investigated. We examined the significance of cervical elastography in the last trimester of pregnancy. Cervical elastography was performed at weekly checkups after 36 weeks of gestation in 238 cases delivered at our hospital from 2017 to 2018. The correlation with the onset time of natural labor, which is an index for judging maternal delivery preparation status, was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, studies have reported that cervical elastography performed during pregnancy shows cervical softening and maturation (especially in the internal cervical os) [15,16]. Yo et al performed weekly cervical elastography by starting at the 36th week on 238 pregnant women and found cervical elastography at the 39th gestational week to be useful to evaluate the time of delivery [17]. Lu et al reported that shear wave elastography had a higher estimation accuracy than BS-based models as a result of labor induction [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have reported that cervical elastography performed during pregnancy shows cervical softening and maturation (especially in the internal cervical os) [15,16]. Yo et al performed weekly cervical elastography by starting at the 36th week on 238 pregnant women and found cervical elastography at the 39th gestational week to be useful to evaluate the time of delivery [17]. Lu et al reported that shear wave elastography had a higher estimation accuracy than BS-based models as a result of labor induction [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although other measures of cervical consistency such as elastography exist, they are not currently in common use. [27][28][29] Further research to characterize the predictive value of these objective cervical measures in the late third trimester may help improve the prediction of spontaneous labor onset. Further research is also needed to delineate biological pathways that may explain the association between substance use and spontaneous labor onset.…”
Section: Research Implicationsmentioning
confidence: 99%
“…USE is an established method for evaluating cervical softening, predicting pre-term delivery and outcomes of labor induction [ 64 75 ]. In 2019, a meta-analysis including 1488 pregnant indicated that cervical USE is useful to PTD with a summary sensitivity of 0.84 [95% confidence interval (CI): 0.68, 0.93], a specificity of 0.82 (95% CI: 0.63, 0.93), a diagnostic odds ratio of 25 (95% CI: 7, 93), and AUC of USE being 0.90 (95% CI: 0.87–0.93) [ 76 ].…”
Section: Predicting Preterm Deliverymentioning
confidence: 99%